Information security threats encountered by Malaysian public sector data centers - Inthrani Shammugam; Ganthan Narayana Samy; Pritheega Magalingam; Nurazean Maarop; Sundresan Perumal; Bharanidharan Shanmugam (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Data centers are primarily the main targets of cybercriminals and security threats as they host various critical information and communication technology (ICT) services. Identifying the threats and managing the risks associated with data centers have become a major challenge as this will enable organizations to optimize their resources to focus on the most hazardous threats to prevent the potential risks and damages. The objective of this paper is to identify major ICT security threats to data centers in the Malaysian public sector and their causes. The data for this study was collected through interview sessions. A total of 33 respondents from various government organizations were interviewed. The results revealed that the technical threats, spyware, phishing, bluesnarfing threats, social engineering and virus, trojan, malware, ransomware, viral websites threats are the major categories of threats often encountered by the malaysian public sector organizations. The causes for these threats are lack of budget, competent personnel, and manpower for security tasks, user awareness; lack of compliances and monitoring; insufficient security policies and procedures as well as deliberate cyber attacks. The outcome of this study will give a greater degree of awareness and understanding to the ICT security officers, who are entrusted with data center security.